Teaching alternative perspectives of microeconomics - Mat Ghani, Gairuzazmi (Centre for Islamic Economics, IIUM & International Institute of Islamic Thought, 2024)
“The degree to which economics is isolated from the ordinary business of life is extraordinary and unfortunate.” —Ronald Coase